Pengaruh Motivasi Kerja dan Komitmen Organisasi Terhadap Kinerja Karyawan PT. BPR Syariah Lantabur Tebuireng di Jombang - Wahyu Dwi Lestari; Mahfudiyanto Mahfudiyanto (BIMA : Journal of Business and Innovation Management, 2021)
Good employee performance must be maintained to complete duties and responsibilities for the creation of company goals, where work motivation and organizational commitment are the driving force. This research uses quantitative research and causal types. The population of this research is all employees of PT. BPRS Lantabur Tebuireng in the Jombang area. The tests used are: hypothesis test, classic assumption test, R2 test and multiple linear regression analysis. The results showed that: 1) work motivation partially has no effect on employee performance, resulting in a probability value of 0.143. 2) organizational commitment partially affects employee performance, resulting in a probability value of 0.00. 3). Meanwhile, work motivation and organizational commitment have a simultaneous effect on employee performance, with a probability value of 0.00.